Developing a Wireless Network for Optimum Distance Learning Assistant - Dr.M.Prabha; Dr. Sudhir Anakal; Dr. Poornachandran R; Raghavendra M Ichangi; Dr S Someshwar; Dr.R.Senthamil Selvan (The Bioscan, 2024)
A new wireless network-based distant education auxiliary system is developed to address the issues of low operational efficiency, slow reaction times, and unstable systems. Develop the hardware component of the system's business process and enhance the functionalities of the subsystems. The subsystem encompasses course information enquiries, administration of instructors and in-person teaching processes, and plan management, among other functions. To enhance the implementation of linked hardware applications, audio and video signals are integrated in software design via the combination of signal coding technologies, using MMX technology for synchronous processing. The testing findings indicate that the developed system may significantly decrease reaction time and enhance stability. This research establishes a robust framework for the steady functioning of a distance education auxiliary methods and achieves the optimisation of a distance education auxiliary systems.